Meta‐analysis of retroperitoneal vs transperitoneal laparoscopic and robot‐assisted pyeloplasty for the management of pelvi‐ureteric junction obstruction. (13th November 2020) - Chua, Michael E.; Ming, Jessica M.; Kim, Jin Kyu; Milford, Karen L.; Silangcruz, Jan Michael; Ren, Lily; Rickard, Mandy; Lorenzo, Armando J.
Abstract : Objective: To determine differences in perioperative outcomes between retroperitoneal and transperitoneal approaches for laparoscopic pyeloplasty (LP) to manage pelvi‐ureteric junction obstruction (PUJO) through a meta‐analysis of comparative studies. Methods: A systematic search was performed in January 2020. Comparative studies were evaluated according to Cochrane Collaboration recommendations. Assessed outcomes included success and complication rates, conversion to open surgery, operative time (OT), length of hospital stay (LOS), estimated blood loss (EBL), analgesic requirements, regular diet resumption, and drain duration. Relative risk (RR) and standardised mean difference (SMD) with 95% confidence intervals (CIs) were extrapolated. Subgroup analyses were performed according to study design and techniques. International Prospective Register of Systematic Reviews (PROSPERO) number: CRD42020163303. Results: A total of 18 studies describing 2007 cases were included. Overall pooled effect estimates did not show statistically significant differences between the approaches with regards to success rate (RR 0.99; 95% CI 0.97, 1.01), complications (RR 1.09; 95% CI 0.82, 1.45), OT (SMD 0.61; 95% CI −0.04, 1.26), LOS (SMD −0.30; 95% CI −0.63, 0.04), EBL (SMD −0.53; 95% CI −1.26, 0.21), or analgesic requirements (SMD −0.51; 95% CI −1.23, 0.21). Compared to the transperitoneal approach, retroperitoneal LP had a higher conversion rate (RR 2.40; 95% CI 1.23, 4.66); however, patients resumed diets earlier (SMD −2.49; 95% CI −4.17, −0.82) and had shorter drain duration (SMD −0.31; 95% CI −0.57, −0.05). Conclusion: The evidence suggests that there are no significant differences in success rate, OT and complications between transperitoneal and retroperitoneal LP. Conversion rates are higher with the retroperitoneal approach; however, return to diet occurs faster and drain duration is shorter when compared to the transperitoneal approach.